The Association between Socioeconomic Status with Knowledge, Attitude and Practice toward Use of Iron and Vitamin A-D Supplements among Infants and Pregnants: The NUTRI-KAP survey - Forouzan SALEHI; Zahra ABDOLLAHI; Zeinab AHADI; Mostafa QORBANI; Gita SHAFIEE; Shayesteh KHOSRAVI; Maryam SANAEI; Mina MINAEI; Ramin HESHMAT (Tehran University of Medical Sciences, 2015)
Background: The goal of the current study was to investigate the association between socioeconomic status (SES) and knowledge, attitude and practice (KAP) of Iranian households toward use of iron and vitamin A&D supplements in infants and pregnant women. Method: Overall, 14,136 Iranian households from urban and rural areas of 31 provinces were considered as the study population. A multi-stage cluster sampling technique was applied in each province and the size of clusters was 8 people. Data were collected by interviewing the qualified person and using a structure questionnaire. Socioeconomic status was considered as three levels (good, moderate or weak) based on five variables: household assets, occupation and education levels of head of family and respondent and number of family members. The percentage of KAP in households was measured by questions about essential supplementation in pregnancy and infancy. Result: The percentage of knowledge of using vitamin A&D and the beginning time of iron intake was 67.4%, and 67.8%, respectively. More than three forth of respondents had a favorable attitude about iron intake in pregnancy and infancy. Almost 80% of households used iron and vitamin A&D for their infants and 78% of pregnant women used iron supplement. Generally, the percentage of KAP was significantly higher in urban households. There was a linear association between KAP and SES. Conclusion: KAP in urban and rural households was not desirable; however, urban households had better status than rural ones. One of the suggested ways of ameliorating nutritional issues in pregnant women and infants aged less than two years olds is educating households about the importance of supplementation in pregnancy and infancy.   Keywords: Socioeconomic status, Knowledge, Attitude, Practice, Iron, Vitamin A-D